2022
DOI: 10.32609/0042-8736-2022-3-118-131
|View full text |Cite
|
Sign up to set email alerts
|

Settlement and regional differences in the impact of the food embargo on household consumer spending

Abstract: This study examines the impact of food counter‑sanctions introduced in 2014 and the accompanying shock price hike on consumer spending in Russian households. Moscow residents were studied separately as being mostly inclined to consume imported products, for whom the real total gap with potential consumer spending was estimated at 4,600 rub. per month per family, which is 2,2 times higher than the same indicator for the regions. Importantly, for the residents of Moscow the most deviating from the scenario traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Berendeeva and Ratnikova have conducted a comparative study of the effects of changes in price and supply (substitution effects) [11]. They found that the trends differed in rural and urban areas.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Berendeeva and Ratnikova have conducted a comparative study of the effects of changes in price and supply (substitution effects) [11]. They found that the trends differed in rural and urban areas.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They found that the trends differed in rural and urban areas. For example, in cities, the market for fruit and vegetables has undergone much more significant changes than in rural areas, where residents have their own gardens [11]. According to the researchers, the transformations in the capital regions also differed from those in other territories of the country, since until 2014 the share of imported products was higher there.…”
Section: Previous Studiesmentioning
confidence: 99%